2019
DOI: 10.1039/c9ra01060b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of poly(ethylene glycol)-grafted graphene on the electrical properties of poly(lactic acid) nanocomposites

Abstract: Maleic anhydride was reacted with the armchair edges of graphene nanosheets (GN) via Diels-Alder reaction. Then, polyethylene glycol (PEG) was grafted onto the GN in the presence of anhydride groups through an esterification reaction. The PEG-grafted GN (PEG-g-GN) was characterised via FTIR analysis, thermogravimetric analysis, scanning electron microscopy, Raman spectroscopy and contact angle measurements, proving that PEG was successfully grafted onto the GN surface. The results indicated that PEG-g-GN posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…The electrical conductivity of PEG-GO-based polymer composites was reported in a recent study. 80 PEG grafted graphene nanosheets (PEG-g-GN) were uniformly dispersed in polylactic acid (PLA). The composite exhibited tensile strength of 59.46 MPa with conductivity of 9.69 ± 10 −4 S cm −1 .…”
Section: Cardiac Tissue Engineeringmentioning
confidence: 99%
“…The electrical conductivity of PEG-GO-based polymer composites was reported in a recent study. 80 PEG grafted graphene nanosheets (PEG-g-GN) were uniformly dispersed in polylactic acid (PLA). The composite exhibited tensile strength of 59.46 MPa with conductivity of 9.69 ± 10 −4 S cm −1 .…”
Section: Cardiac Tissue Engineeringmentioning
confidence: 99%
“…
Figure 9. Comparison of the toughening effect of graphene-type nanofillers on PLA [ 20 , 21 , 32 , 45 52 ].
…”
Section: Resultsmentioning
confidence: 99%
“…The SEM micrographs (low magnification) of the pure PLA and PLA/GC-g-PEG 0.3 nanocomposites tensile fracture surfaces can also be seen in the electronic supplementary material, figure S5. PEG/PEGmGO [21] PEG/g-GN [45] TPCS-GRH [46] EG [47] GO-ZnO [48] NGP [49] TRG/Py-PEG [50] GnP/CFX [51] graphene/PVA [52] GO-g-PLLA [20] GO-ODAG [32] This work tensile strength (MPa) Figure 9. Comparison of the toughening effect of graphene-type nanofillers on PLA [20,21,32,[45][46][47][48][49][50][51][52].…”
Section: Samplesmentioning
confidence: 99%
“…In addition, thermal and flammability properties of CNT and graphite filled rigid polyurethane composites have been studied and it was found that both CNT and graphite have a minor impact on the decomposition process during thermal degradation of polyurethane [72]. Further, poly(lactic acid) composites prepared with polyethylene glycol grafted graphene (PEG-g-GN) showed significant improvement of tensile strength and at 1 wt% PEG-g-GN showed the highest property improvement due to the improvement of compatibility between poly(lactic acid) and GN [73]. Moreover, properties of thermally exfoliated and partially reduced GO (TERGO) and GO filled polylactide and polycaprolactone composites have been studied and they have been utilized for thermal management and other packaging applications [74].…”
Section: Applications Of Groups Of Graphite Derivativesmentioning
confidence: 99%
“…to incorporate into NR [42]. In a recent study, Huang et al, [77] synthesized polyethylene glycol grafted graphene (PEG-g-GN) to enhance electrical properties of poly (lactic acid) nanocomposite due to poor adhesion of unmodified natural graphite [77]. Further, mechanical and chemical resistance of GO, rGO and bentonite clay incorporated NR composites [42] have been evaluated and remarkable improvement of tensile strength was found in NR/rGO composite.…”
Section: Graphite Derivatives-based Natural Rubber Compositesmentioning
confidence: 99%